Characteristics and short- and long-term direct medical costs among adults with timely and delayed presentation for HIV care in the Netherlands - Popping, Stephanie; Versteegh, Lisbeth; Nichols, Brooke E.; van de Vijver, David A. M. C.; van Sighem, Ard; Reiss, Peter; Geerlings, Suzanne; Boucher, Charles A. B.; Verbon, Annelies (PloS one, 2023)
In Europe, half of people living with HIV (PLWH) present late to care, with associated higher morbidity and mortality. This study aims to assess short- and long-term costs of HIV-care based on time of presentation and identify other factors contributing to higher costs in the first and fifth year after antiretroviral therapy (ART) initiation. We included ATHENA cohort data which prospectively includes 98% of PLWH in the Netherlands. PLWH who initiated ART in 2013 were included and followed over five years. PLWH were divided in three categories based on CD4 cell-count at time of ART initiation: timely presentation (CD4>350cells/μL), late presentation (CD4 200-350cells/μL or >350cells/μL with AIDS-defining illness) and very late presentation (CD4<200cells/μL). The total HIV-care cost was calculated distinguishing ART medication and non-ART medication costs (hospitalization, outpatient clinic visits, co-medications, and HIV-laboratory tests). From 1,296 PLWH, 273 (21%) presented late and 179 (14%) very late. Nearly half of those who entered HIV-care in a very late stage were of non-Dutch origin, with 21% originating from sub-Saharan Africa. The mean cost per patient in the first year was €12,902 (SD€11,098), of which about two-thirds due to ART (€8,250 (SD€3,142)). ART costs in the first and fifth year were comparable regardless of time of presentation. During the first year on treatment, non-ART medication costs were substantially higher among those with late presentation (€4,749 (SD€8,009)) and very late presentation (€15,886 (SD€ 21,834)), compared with timely presentation (€2,407(SD€4,511)). Higher non-ART costs were attributable to hospitalization and co-medication. The total non-ART costs incurred across five years on treatment were 56% and 246% higher for late and very late presentation respectively as compared to timely presentation. Very late presentation is associated with substantial costs, with non-ART costs nearly seven times higher than for those presenting timely. Hospitalization and co-medication costs are likely to continue to drive higher costs for individuals with late presentation into the future. Programs that identify individuals earlier will therefore likely provide significant short- and long-term health cost savings.